ASSESSMENT ON HYDROTHERMAL PARTICLE CHEMISTRY FROM A SHALLOW VENTING SYSTEM OFFSHORE KOS, AEGEAN SEA - Megalovasilis, P. (Bulletin of the Geological Society of Greece, 2016)
Shallow submarine hydrothermal vents along Hellenic Volcanic Arc transfer significant quantities of particles enriched in basic metals. Fluids collected by scuba diving from two shallow hydrothermal venting areas on Kos Island in the Aegean Sea in East Mediterranean. Samples were filtrated and membrane filters leached with a mixture of acids. Chemical analysis performed in suspended particles for Fe, Mn, Cu, Pb, Cd, Ca, Ba, Sr, Li, Al and Si. The suspended particulate matter (SPM) flux varied from 0.93 to 8.64 mg/l and between 0.21 and 20.94 mg/l in two sites. Metal/Al ratios also vary significantly within a short distance. The pH of hydrothermal waters was from 5.50 to 5.95 in Kephalos Bay and from 6.09 to 6.53 in Bros Thermi suggesting gases CO2 and H2S may control pH values. Particles were dominated by Fe, Ca, Si and Al and strongly enriched in Mn, Cu, Pb and Ba. Three geochemical groups were identified being associated with distinct hydrothermal processes concerning sulphide minerals, carbonate substrate and deeper Al-Silicate rock basement